1990
DOI: 10.1177/027614679001000103
|View full text |Cite
|
Sign up to set email alerts
|

The Ethics of Virtue: A Moral Theory for Marketing

Abstract: The moral theory of virtue ethics holds much promise for guiding the behavior of marketers. Although the origins of this theory can be traced back to Aristotle, it has not received as much emphasis as the teleological and deontological theories within marketing. In the ethics of virtue, traits such as compassion, fairness, loyalty, and openness shape a person's and an organization's vision. Several marketing situations confronted by Johnson & Johnson are used to illustrate the theory of virtue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 14 publications
1
62
0
1
Order By: Relevance
“…In addition to practicing good habits and placing emphasis on individual/corporate character, other features of virtue ethics include the importance of imitating ethical behavior of mentors/elders, that virtues are learned and practiced and that the aspirations of the community are a big motivator. Still another aspect of the virtue approach is the "ethic of the mean" which states that practitioners of virtue ethics succeed by seeking balance in their lives (for more complete discussion of virtue ethics in marketing, see Murphy, 1999;Murphy et al, 2005;Williams and Murphy, 1992).…”
Section: Virtue Ethics In Relationship Marketingmentioning
confidence: 99%
“…In addition to practicing good habits and placing emphasis on individual/corporate character, other features of virtue ethics include the importance of imitating ethical behavior of mentors/elders, that virtues are learned and practiced and that the aspirations of the community are a big motivator. Still another aspect of the virtue approach is the "ethic of the mean" which states that practitioners of virtue ethics succeed by seeking balance in their lives (for more complete discussion of virtue ethics in marketing, see Murphy, 1999;Murphy et al, 2005;Williams and Murphy, 1992).…”
Section: Virtue Ethics In Relationship Marketingmentioning
confidence: 99%
“…Reciprocity is an essential component of the relationship commitment which requires equivalent response to the other parties' actions. Williams and Murphy (1990) also found that one feature of persuasive promotion is to avoid invading the customer's autonomy. Moreover, Abela and Murphy (2008) also found that ethical issues are still a serious problem in today's marketing and business practices and have been since the 1950s.…”
Section: Autonomy and Relationship Longevitymentioning
confidence: 99%
“…Thus, ethics can be applied to each element of the marketing mix, namely, product, price, distribution and promotion (Takala & Uusitalo, 1996). Furthermore, Williams and Murphy (1990) indicated the need for principles and standards that guide managers and firms in making decisions and setting priorities in addition to stressing that ethics in marketing is an international trait that can be applied across different cultures. Normally, ethical problems arise in new marketing practices owing to the seller focusing on financial issues while ignoring ethical issues (Majtán & Dubcová, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 1990, three literature reviews in research (Kahn 1990), teaching (Furman 1990) and marketing (Williams & Murphy 1990) were published, and none made reference to virtues. They all coincided, however, in citing utilitarianism (or "teleology") and Kantian deontology as dominant theories.…”
Section: The Novelty Of Virtue Ethicsmentioning
confidence: 99%
“…Not content with utilitarianism and deontology, they turn to virtue ethics with its notion of a "golden mean". Williams and Murphy (1990) …”
Section: : Virtue Ethics' First Appearance In Marketingmentioning
confidence: 99%